Application of telenursing as a nursing care delivery model in improving treatment adherence and glycemic control: A scoping review - Yuli Wahyuni; Maria Komariah; Irman Somantri (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Diabetes mellitus is one of the chronic diseases that cause the highest mortality and high medical costs;, therefore medication adherence and glycemic control are important in disease management, one of which is through telenursing. Purpose: To determine the telenursing model to improve medication adherence and glycemic control in patients with type 2 diabetes mellitus. Methods: This study was designed a scoping review. The databases used are CINAHL, PubMed, ScienceDirect and Google Scholar. Articles published from 2016-2022 with appropriate inclusion and exclusion criteria. Thematic analysis was used based on study design, telenursing communication model, telenursing process, duration of telenursing and results. Results: There were 12 relevant articles out of 2112 articles. We found a telephone call follow up is the most common method used for delivery of telenursing intervention. Telenursing intervention is implemented from at least 3 months until 12 months, and includes the assessment of current disease conditions, assessment of adherence to the prescribed treatment plan, treatment plan information, and solutions or follow-up to current issue. Conclusion: Telenursing can be used as a nursing care delivery model in the diabetes mellitus type 2 patients because it is proven to reduce glycemic control, improve treatment adherence, reduce body mass index (BMI), glycosylated hemoglobin (HbA1c), and cholesterol, and improve diet adherence, physical exercise and self-management.